Pengaruh Jenis dan Konsentrasi Matriks Terhadap Profil Pelepasan Obat pada Sediaan Tablet Lepas Lambat - Wilda Tsabitah Jafnah Mahmud; Wishnu Eka Adiwinata; Alya Miladiyah Chayani; Salsha Bila Dwi Lestari; Elit Juwita Ratu; Haya Avia Aunillah; Dewi Rahmawati; Yani Ambari; Dzakiya Zhihrotul Wida (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Sustained-release tablets are pharmaceutical preparations designed to release active ingredients gradually and in a controlled manner over a longer period of time. The type and concentration of the matrix used are the main determining factors in controlling the drug release profile. This study aims to examine the effect of various types and concentrations of matrices on the drug release profile in sustained-release tablets based on scientific literature published between 2011 and 2025. This study used a literature review method (review article) by collecting and analyzing ten scientific articles from Google Scholar, PubMed, and Scopus databases. The results of the study showed that hydrophilic matrices such as Hydroxypropyl Methylcellulose (HPMC), xanthan gum, and pectin proved to be the most effective in controlling drug release through a gel layer formation mechanism. Increasing the concentration of hydrophilic polymers generally slows the rate of drug release by forming a thicker and more stable gel. Hydrophobic matrices such as ethyl cellulose provide release control through a pore diffusion mechanism that produces a profile approaching zero-order kinetics. In contrast, modified starch-based matrices such as phosphate-cross-linked pregelatinized sago starch and glucomannan have not demonstrated adequate release control. Combinations of two polymers, such as HPMC-xanthan gum and HPMCAS-HPC, have been shown to produce more stable and controlled release profiles than either polymer alone. These findings suggest that the selection of matrix type and concentration should consider the physicochemical properties of the drug, the desired release control mechanism, and dissolution requirements based on the drug's pharmacokinetic profile.